ANALISIS HAK PRIVASI PERLINDUNGAN DATA PRIBADI MASYARAKAT DI INDONESIA - Jennifer Claudia; Toendjoeng Herning Sitaboeana (Jurnal Hukum Adigama, 2021)
The more big and updated progress in technology, the more new challenges show up and that affects the protection of citizens' privacy and personal data, especially with the increasing practice of collection, use and dissemination of personal data or the problem known as the data misuse. Other than lack of specific regulations that may cause the weakness of privacy and personal data protection even more, especially when it comes to the use of technology. There is also known as the cloud computing technology which is a technology that uses the internet and central remote servers to maintain or manage user data. It allows users to use applications without installation such as via website, links, etc. so the personal data can be accessed anywhere and anytime through the internet access. But some legal issues in the world of technology are raised by cloud computing technology. The legal issue from cloud computing is very noticeable and dangerous because the personal data contains personal information such as full name, date of birth, id card number, etc. Which means if the provider or the third party, misused the personal data, it is a crime in the eye of law and it is wrong to human rights. As a country, Indonesia does have regulations that specifically protect the citizens from data abuse or known data misuse. But this is not how personal data is protected in Indonesia.